IMPROVING THE MECHANICAL PROPERTIES OF CARBON-EPOXY AND GLASS-EPOXY COMPOSITES BY INCORPORATING SILICA NANOPARTICLES - DAWOOD, THAKER S.; FADHIL, BASIM M.; RAMADAN, DLAIR O. (Journal of Duhok University, 2023)
Hybrid composite materials possess significant potential as engineering materials across various application sectors such as construction, automotive, marine, and aerospace. They provide designers with the ability to achieve desired properties to a considerable extent by carefully selecting both the fibers and matrix used. By incorporating different types of fibers into a common resin matrix, the material’s properties can be customized and tailored accordingly. In this study, the mechanical properties of glass and carbon fiber epoxy composites that were strengthened with silica nanoparticles were looked at and compared to those of plain epoxy to figure out how well they could be used in structural applications. Regardless of the laminated material, the samples were manufactured using the vacuum bag method and heat-cured. Mechanical properties such as E1, E2, G12, and ν12 were determined using the tensile test and the relevant ASTM standards to ensure accurate and reliable results. Experimental and numerical modeling will be employed to assess significant differences between the glassy epoxy and carbon epoxy composites in terms of their mechanical properties. The results of this study show that adding 2% wt of SiO2 nanoparticles to composite materials improves their mechanical properties. The tensile strength of the glass composite went up by 5.74 percent, and the tensile strength of the carbon composite went up by 13.51 percent.